Kelayakan LKPD Berbasis Discovery Learning Materi Struktur dan Fungsi Jaringan pada Tumbuhan - Ningsih, Kurnia; Ganda Putri Panjaitan, Ruqiah; Marina, Marina (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to determine the feasibility of student worksheets based on discovery learning on the structure and function of tissue in class XI plants. The method used in this research is Research and Development (R&D) or research and development. Data analysis using Content Validation Rate (CVR) and Content Validation Index (CVI) refers to the Lawshe method. The validator involved two lecturers of biology education, and three biology teachers. There are 3 aspects of the assessment, namely learning three criteria, learning content of five criteria and displaying five evaluation criteria. Based on the results of data analysis, all the CVR criteria are 0.99 in the valid category and the CVI is 0.99. It can be concluded that the student worksheets based on discovery learning on the structure and function of tissue is suitable for use as teaching materials in high school.Because this research only reached the validation and design revision stage, the researcher suggests to future researchers to carry out the research stage to the end, namely mass production, with the aim that the resulting product can help teachers and students in the teaching and learning process.